Sex-specific associations of muscular fitness with overall academic performance and specific school subjects in adolescents: the EHDLA study - Manzano-Sánchez, David; Gutiérrez-Espinoza, Héctor; López-Gil, José Francisco (Frontiers in Psychology, 2024)
Introduction Overalll, muscular fitness and academic performance are two variables widely studied in the literature. However, evidence on the relationship between muscular fitness and specific school subjects (e.g., physical education), as well as their differences by sex, is scarce. Objective The aim of this study was to examine the associations between muscular fitness and overall academic performance and between muscular fitness and specific subjects (i.e., language, math, foreign language, and physical education) in a sample of secondary Spanish school students. Methods For the present study, a sample of 766 students (45% boys, aged 12-17 years). From the Eating Healthy and Daily Life Activities (EHDLA) study was used. The Assessing the Levels of Physical Activity and Fitness (ALPHA-FIT) battery was used to determine handgrip strength and lower body muscular strength. The performance of the different school subjects was provided by the school centers. Results Overall, for both boys and girls, higher muscular fitness was associated with greater academic results, with the greatest differences in physical education. However, only significant differences were identified for girls. Discussion and conclusion Global muscular fitness is important for contributing to cognitive development, both in physical education and in the rest of the subjects of the educational curriculum for adolescents. At the same time, although the association appears to follow the same trend for both sexes, the results seem more evident for girls.